Outlook of first year medical students in a Government Medical College in Mysuru - K., Manasa; R., Mythily M.; Khan, Mudassir Azeez (International Journal Of Community Medicine And Public Health, 2021)
Background: The medical field has been one of the top choices for students. It is one of the promising career choice but along with it the students have to go through long period of course and hard work. The aspirations and perception of students are important to make necessary changes in curriculum and work settings which in turn leads to quality output. Methods: The study was conducted among the first year medical students in the government medical college Mysore. The proforma included details about demographic characteristics and influencing factors to choose medical field. Results: Among 143 students, 97 were males and 46 females. 91 students entered the course in first attempt and 52 students in the subsequent attempts. The most important influencing factors to enter medical field were doing service, passion for the profession and parents wish. Conclusions: Self interest in medical field was main reason for joining course. Majority of the students were happy, proud but also felt fear and anxiety on joining the course.